Pound, Williams selected letters of Ezra Pound and William Carlos Williams - Pound, Ezra 1885-1972; Williams, William Carlos 1883-1963 (New Directions Publ., 1996)
Ezra Pound and William Carlos Williams, two towering figures in American poetry, began their lifelong, and often contentious, friendship as students at the University of Pennsylvania. Their correspondence ran from 1907, the year Pound took up his virtually permanent residence in Europe, until Williams' death in 1963. The letters contribute an unparalleled documentary record of modern culture - a wealth of information about the lives and works of the two poets themselves; the literary and political movements in which they became involved and the impact of public events upon the arts; the activities of other writers and artists; and the world of small presses and little magazines that nourished the growth of modernism. Pound/Williams contains 169 letters selected from the poets' surviving correspondence, each letter reproduced in full and accompanied by explanatory notes. Historical introductions place each of the live chronological groupings of letters into context, and a biographical glossary identifies persons prominently mentioned.
Keywords: Pound, Ezra <1885-1972> -- Correspondence; Williams, William Carlos <1883-1963> -- Correspondence; Williams, William Carlos -- 1883-1963; Pound, Ezra -- 1885-1972; Geschichte 1900-2000; Critics -- United States -- Correspondence; Poets, American -- 20th century -- Correspondence; USA; Briefsammlung